1998
DOI: 10.1021/jo981396o
|View full text |Cite
|
Sign up to set email alerts
|

Cp2VCl2-Catalyzed Meso-Selective Pinacol Coupling Reaction of Aldimines in the Presence of Chlorosilane and Zinc Metal

Abstract: A catalytic reductive coupling of aldimines was achieved by using a catalyst Cp2VCl2/PhMe2SiCl/Zn system. The influence of the catalyst, chlorosilane, co-reductant, solvent, and temperature on both the yield and diastereoselectivity of the coupling products was investigated in detail. As a result, the present Cp2VCl2-catalyzed reductive coupling of aldimines in the presence of PhMe2SiCl and zinc metal provided the corresponding 1,2-diamines in good yield with high meso selectivity (up to 92% meso), while the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 16 publications
1
24
0
2
Order By: Relevance
“…In accordance with a chelated transition state, the anti-configurated products are predominantly formed, albeit with low diastereoselectivity: At best, an anti/syn ratio of 4.3:1 was observed. The relative configuration of the main products could be determined based on the reported characteristic 1 H and 13 C chemical shifts of vicinal diamines as well as the NOE data of the diastereomeric formaldehyde aminals of the diamines 4 a and 4 m. [19][20][21][22] In attempts to improve the diastereoselectivity of the reduction, we found that the reaction of the pure diimines 3 with BH 3 ·THF containing NaBH 4 furnishes preferentially the syn-configurated diamines 4 in quantitative yield (Table 2, Method A). Compounds of this type may be applied as combinatorially diverse pseudo-C 2 -symmetric N,N ligands for asymmetric aldol reactions, [23] dihydroxylations, [24] and reductions.…”
mentioning
confidence: 99%
“…In accordance with a chelated transition state, the anti-configurated products are predominantly formed, albeit with low diastereoselectivity: At best, an anti/syn ratio of 4.3:1 was observed. The relative configuration of the main products could be determined based on the reported characteristic 1 H and 13 C chemical shifts of vicinal diamines as well as the NOE data of the diastereomeric formaldehyde aminals of the diamines 4 a and 4 m. [19][20][21][22] In attempts to improve the diastereoselectivity of the reduction, we found that the reaction of the pure diimines 3 with BH 3 ·THF containing NaBH 4 furnishes preferentially the syn-configurated diamines 4 in quantitative yield (Table 2, Method A). Compounds of this type may be applied as combinatorially diverse pseudo-C 2 -symmetric N,N ligands for asymmetric aldol reactions, [23] dihydroxylations, [24] and reductions.…”
mentioning
confidence: 99%
“…Die Konfiguration der Hauptprodukte konnte mithilfe der in der Literatur beschriebenen charakteristischen 1 H-und 13 C-chemischen Verschiebungen sowie vergleichender NOE-Messungen an den diastereomeren FormaldehydAminalen der Diamine 4 a und 4 m zugeordnet werden. [19][20][21][22] Bei Versuchen zur Erhöhung der Diastereoselektivität der Reduktion fanden wir, dass über den Umweg einer Oxidation der Additionsprodukte zu den Diiminen 3 die synkonfigurierten Diamine 4 erhalten werden können, wenn [23] Dihydroxylierungen [24] oder Reduktionen [25] verwendet werden können. Setzt man bei der Reduktion mit BH 3 ·THF statt NaBH 4 Phthalsäure zu (Tabelle 2, Methode B), [26] entstehen hingegen die anti-konfigurierten Produkte.…”
unclassified
“…Few general routes exist for their diasteroselective preparations. 2 As part of our ongoing program it is of interest to study the crystal structure of the title compound ( Fig. 1).…”
mentioning
confidence: 99%
“…The stereochemistry was assigned by comparing the resonances of the benzylic protons, as reported in the literature. 2 The molecular structure of the title compound appeared as shown in Fig. 2.…”
mentioning
confidence: 99%